Nitrogen dilution effect for small angle GDH experiment in JLab Hall-A - 吕海江 叶云秀 闫新虎 程和平 焦铮 何聚 刘仁臣 (Chinese physics C, 2008)
In the GDH sum rule measurement in JLab Hall-A, to obtain the cross section of electron scattering on polarized 3^He and its asymmetry in different helicity states, the dilution effect from unpolarized nitrogen mixed in the polarized 3^He target were calculated at different kinematic settings.